‘Mind the Gap’—reforestation needs vs. reforestation capacity in the western United States - Dobrowski, Solomon Z.; Aghai, Matthew M.; Chichilnisky du Lac, Ariella; Downer, Rebecca; Fargione, Joseph; Haase, Diane L.; Hoecker, Tyler; Kildisheva, Olga A.; Murdoch, Alix; Newman, Shaw; North, Malcolm; Saksa, Phil; et al. (Frontiers in Forests and Global Change, 2024)
Tree establishment following severe or stand-replacing disturbance is critical for achieving U.S. climate change mitigation goals and for maintaining the co-benefits of intact forest ecosystems. In many contexts, natural post-fire tree regeneration is sufficient to maintain forest cover and associated ecosystem services, but increasingly the pattern and scale of disturbance exceeds ecological thresholds and active reforestation may be warranted. Our capacity to plant trees, however, is not keeping pace with reforestation needs. This shortfall is uniquely apparent in the western U.S., where wildfire size and severity have increased in recent decades and long-term divestment in the reforestation supply chain has limited our ability to respond to existing needs. Here we present an analysis of key facets of both the supply and demand side of reforestation in the western U.S. and address six questions: 1) What is the current backlog of potential reforestation needs driven by highseverity wildfire?; 2) How will increasing wildfire activity through the end of the century affect potential reforestation needs?; 3) What is our capacity to meet current and future reforestation needs?; 4) How can we scale the reforestation supply chain to meet current and future demands?; 5) What approaches to reforestation can promote forest resilience to climate change and wildfire?; and 6) Where are opportunities emerging from recent policy initiatives, innovative public-private partnerships, and natural capital markets for scaling reforestation?Between 1984 and 2000, annual tree planting capacity met post-fire needs but cumulatively over the last two decades (2000 to 2021) it has fallen short of fire-driven needs by an estimated 1.5 million ha (ca. 3.8 million ac). We anticipate this gap will increase 2 to 3 fold by 2050. Scaling up reforestation efforts to close this gap will require increased investment across all facets of the reforestation supply chain, public-private partnerships, and novel approaches to reforestation that increase the resilience of western forests to drought and wildfire. We highlight emerging opportunities from recent policy initiatives and conservation finance for expanding reforestation efforts.